2015
DOI: 10.1007/s12264-015-1555-3
|View full text |Cite
|
Sign up to set email alerts
|

Clemastine rescues behavioral changes and enhances remyelination in the cuprizone mouse model of demyelination

Abstract: Increasing evidence suggests that white matter disorders based on myelin sheath impairment may underlie the neuropathological changes in schizophrenia. But it is unknown whether enhancing remyelination is a beneficial approach to schizophrenia. To investigate this hypothesis, we used clemastine, an FDA-approved drug with high potency in promoting oligodendroglial differentiation and myelination, on a cuprizone-induced mouse model of demyelination. The mice exposed to cuprizone (0.2% in chow) for 6 weeks displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
106
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(109 citation statements)
references
References 38 publications
3
106
0
Order By: Relevance
“…Preclinical work validated the efficacy of clemastine fumarate in vitro and in animal models. 17,19 Additional work confirmed the efficacy of clemastine fumarate in multiple animal models [17][18][19][20][21][22] and showed that this benefit was mediated specifically via remyelination induced from oligo dendrocyte differentiation and not via effects on the immune system. 19 We furthermore showed the capacity of clemastine fumarate to induce oligodendrocyte progenitor cell (OPC) differentiation and myelination with human OPCs (appendix).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Preclinical work validated the efficacy of clemastine fumarate in vitro and in animal models. 17,19 Additional work confirmed the efficacy of clemastine fumarate in multiple animal models [17][18][19][20][21][22] and showed that this benefit was mediated specifically via remyelination induced from oligo dendrocyte differentiation and not via effects on the immune system. 19 We furthermore showed the capacity of clemastine fumarate to induce oligodendrocyte progenitor cell (OPC) differentiation and myelination with human OPCs (appendix).…”
Section: Introductionmentioning
confidence: 78%
“…Preclinical data unequivocally showed that clemastine fumarate promotes oligodendrocyte precursor differentiation 17,18 and remyelination [19][20][21][22] without modulating the immune system. 19 The robustness of the findings were documented by the latency improvement observed in both groups of the cohort while on active treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Non‐selective muscarinic receptor antagonists promote myelin repair in rodents (Deshmukh et al, ; Mei et al, ). Clemastine, an antimuscarinic compound, rescues behavioral changes and enhances remyelination in a cuprizone mouse model of demyelination (Li et al, ). In these studies, the behaviors analyzed were open field tests and Y‐maze learning, which are considered assays of schizophrenia‐like behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, the behaviors analyzed were open field tests and Y‐maze learning, which are considered assays of schizophrenia‐like behaviors. Clemastine also enhances myelination in the prefrontal cortex and rescues behavioral changes observed in socially isolated mice (Li et al, ; Liu et al, ). Sexual dimorphism is evident in oligodendrocyte development, myelination, and risk for multiple sclerosis (Swamydas, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, identifying small molecule therapies that specifically promote oligodendrocyte differentiation and myelin production is important for the repair process, with the goal of slowing the degeneration of demyelinated axons (Bjartmar & Trapp, 2001). For example, two separate high throughput screens of FDA approved libraries using cultured OPCs independently identified Clemastine, an antihistamine that enhances oligodendrocyte differentiation and myelination in rodents (Li, He, Fan, & Sun, 2015;J. For example, two separate high throughput screens of FDA approved libraries using cultured OPCs independently identified Clemastine, an antihistamine that enhances oligodendrocyte differentiation and myelination in rodents (Li, He, Fan, & Sun, 2015;J.…”
Section: Resultsmentioning
confidence: 99%